ICT and Transport Infrastructure Development - Kyoung-Youn Na; Chang-Ho Yoon (International Telecommunications Society (ITS), 2016)
This paper estimates the non-linear impact of ICT network on motorway contribution to total factor productivity. Using dynamic panel data of OECD member countries, the paper finds that there exists a critical mass of broadband penetration rate which has the property that if this threshold level is reached, there will be an accelerating network effects of motorway extension.
Keywords: O47; O38; 330; ICT convergence; productivity growth; complementarity; infrastructure development